The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.7759/cureus.14029
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo: The Association With Metabolic Syndrome and the Role of Simvastatin as an Immunomodulator

Abstract: Vitiligo is an autoimmune condition primarily affecting the skin where there is destruction of melanocytes characterized by pinkish-white patches on the skin. It is associated with other autoimmune diseases such as thyroid disease, rheumatoid arthritis, diabetes mellitus, and metabolic syndrome. Metabolic syndrome is a constellation of disorders including insulin resistance, hypertension, dyslipidemia, and obesity, and is considered a leading cause of cardiovascular morbidity. Simvastatin is a potent hypolipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
0
10
0
2
Order By: Relevance
“… 95 Also, simvastatin, a statin drug, has been tried as a vitiligo treatment, showing beneficial effects, attributed to its antioxidant and immunomodulating effect. 96 Despite these findings, further studies are needed.…”
Section: Other Emergent Cvd-associated Skin Diseasesmentioning
confidence: 99%
“… 95 Also, simvastatin, a statin drug, has been tried as a vitiligo treatment, showing beneficial effects, attributed to its antioxidant and immunomodulating effect. 96 Despite these findings, further studies are needed.…”
Section: Other Emergent Cvd-associated Skin Diseasesmentioning
confidence: 99%
“…Today, little attention has been paid to the role of environmental factors like diet or PE training or the level of habitual physical activity in vitiligo disease. In fact, to the best of our knowledge, there are no studies focused on PE or habitual physical activity level and vitiligo disease, although several studies with similar etiological factors have consistently identified significant associations between vitiligo (as well as its severity) with MetS ( Ataş and Gönül, 2017 ; Sharma et al, 2017 ; Tanacan and Atakan, 2020 ; Verma et al, 2021 ) or related dysfunctions such as higher blood plasma concentrations of low-density lipoprotein (LDL- cholesterol), low high-density lipoprotein (HDL-cholesterol), and insulin resistance ( Karadag et al, 2011 ; Azzazi et al, 2021 ; Demirbaş et al, 2021 ; D’Arino et al, 2021 ). It is well established that a mainly sedentary lifestyle behavior and poor nutritional patterns are the most important risk factors for the onset of MetS or cholesterol disorders ( Lira et al, 2010 ; Edwardson et al, 2012 ).…”
Section: Overview Of Vitiligo Developmentmentioning
confidence: 99%
“…Vitiligo severity has also been associated with metabolic syndrome (MetS), increasing the prevalence and incidence of MetS or associated disorders such as insulin resistance and hypercholesterolemia ( Ataş and Gönül, 2017 ; Sharma et al, 2017 ; Tanacan and Atakan, 2020 ; Verma et al, 2021 ). Etiologically, MetS are associated with a sedentary lifestyle ( Edwardson et al, 2012 ), cellular inflammation, and OS mechanisms ( Bonomini et al, 2015 ) that may be involved in the onset of vitiligo.…”
Section: Introductionmentioning
confidence: 99%
“…Simvastatin reduces myeloperoxidase-dependent AGE production, inhibiting macrophage RAGE expression. This effect, in turn, may help to stabilize plaques by blocking the release of PGE2-dependent MMPs that cause plaque rupture [ 105 ].…”
Section: Management Of Metabolic Disorders Using Rcsmentioning
confidence: 99%
“…With the increase in evidence of the role of oxidative stress in the etiology of diabetes, there have been studies that cross-link the use of antioxidant Simvastatin against diabetes [ 107 ]. They have demonstrated a significant drop in the level of protein carbonyl groups, a type of AGE product in T2DM patients treated with Simvastatin [ 105 ]. This suggests that simvastatin could protect against protein damage in such patients.…”
Section: Management Of Metabolic Disorders Using Rcsmentioning
confidence: 99%